Pengaruh Pertumbuhan Ekonomi dan Investasi terhadap Pendapatan Asli Daerah Provinsi Jambi Tahun 2000 – 2018 - Nadia Yusma Agasta (Science of Management and Students Research Journal (SMS), 2020)
The purpose of this study is to know: (1) To determine the development and characteristics of economic growth, Investasi & PAD in Jambi Province 2000-2018. (2) To determine and analyze the effect of economic growth dan Investasi simultaneously on PAD in Jambi Province 2000-2018. (3) To determine and analyze the effect of economic growth dan Investasi partially on PAD in Jambi Province in 2000-2018. From the regression model it can be explained: 1. A constant value of -2,919 means that if the independent variable, namely Economic Growth (X1), Investment (X2) is zero (0), the dependent variable PAD (Y) will have a fixed value of -2,919.2. The regression coefficient for the Economic Growth variable (X1) is positive at 1.261, meaning that if the X1 variable has increased by 1 (one) percent while the other variables are considered constant, then the Y variable, namely PAD, will decrease by 1.261.